Unsteady characteristics of compressed air energy storage systems with thermal storage from thermodynamic perspective. (1st April 2022) - Guo, Huan; Xu, Yujie; Zhu, Yilin; Chen, Haisheng; Lin, Xipeng
Abstract: Unsteady characteristics of compressed air energy storage (CAES) systems are critical for optimal system design and operation control. In this paper, a comprehensive unsteady model concerning thermal inertia and volume effect for CAES systems with thermal storage (TS-CAES) is established, in which exergy efficiencies of key processes at each time are focused on to follow performance trajectories, and the control for sliding-pressure and constant-pressure operations is introduced. Meanwhile, a revised system efficiency model is proposed with energy transfer involved in joint chamber between components. Based on the model, the unsteady characteristics of charging process and discharging process of TS-CAES are first studied in depth. The difference between system performance under unsteady and steady operation is discovered, and the influence of unsteady factors, such as volume effect, thermal inertia, air reservoir size and pressure variation range on the system efficiency of TS-CAES system is studied for the first time. Results show that the unsteady effect has evident impact on the variation of operating parameters. For the whole system, the stronger the unsteady effect is, the less system efficiency and energy density are, while the thermal inertia having slight effect on system efficiency. The large air storage reservoir is beneficial to weaken volume effect's influence on system efficiency. The study of pressure-range effect indicates that the system efficiency decreases by an average of 0.95% with the maximum relative storage pressure increasing by 0.1, while the system efficiency decreases about 0.35% with the minimum relative storage pressure decreasing by 0.2. Highlights: A comprehensive unsteady and control model of TS-CAES systems is established. Both volume effect and thermal inertia are considered for CAES dynamic study. Effect of unsteady factors on system dynamic processes and performance is revealed. Unsteady effect of different capacities and pressure ranges of reservoir is compared.